PERBANDINGAN KEUNGGULAN BERSAING RESTORAN WARALABA ASING DAN RESTORAN WARALABA LOKAL - Maulina, Venus (IQTISHODUNA, 2009)
The research construct based on some problems covering the reasons why businessman are prefer to choose franchise rather traditional format, even foreign or domestic franchise and the possibility that franchise could be a distinctive competence. The research has selecting eight variables based on the essence of services marketing theory, which are product, price, place, promotion, process, customer services, franchisor capability and people opinion. The research type is explanatory research and populations of the research are The Franchise Restaurants at Malang. The writer collect data by doing interview spread questionnaires and study document. And we choose purposive sampling techniques which made 5 managers from 5 restaurants become respondent. It is using Mann Whitney U-Test. This research divide franchise restaurant into two groups: foreign group which is represented by Kentucky Fried Chicken, Wendy’s and Pizza Hut; and domestic group which is represented by Es Teler 77 and Wong Solo. In a simultaneous test, the results shows that there’s no significant different between 2 groups. In the other side, the partial test describes that foreign and domestic franchise are lead each other in ten different items. The results reflect that the franchise advantages are the reasons why businessman prefers to choose franchise rather than traditional restaurant. Beside, franchising helps people to avoid three limitations such as limited financial, limited human resources and limited management. It makes the company have ability to operate better than others. That’s why the franchise system could be a distinctive competence.